Ru/MgO-catalysed selective aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Lokhande, Priya; Dhepe, Paresh L.; Wilson, Karen; Lee, Adam F. (Australian Journal of Chemistry - an International Journal for Chemical Science, 2024)
Biomass valorisation through the selective oxidation of carbohydrate and lipid derivatives offers access to an array of platform chemicals through energy- and atom-efficient catalytic processes. Supported metal nanoparticles are promising catalysts for the aerobic selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA), but typically require strong liquid base to achieve high selectivity. Here, we explore the utility of MgO as a solid base support for the Ru-catalysed aerobic oxidation of HMF, obtaining 68% FDCA yield at 160°C and 1.5 MPa of O<span style="box-sizing: inherit; font-size: 11.25px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(0, 49, 60); font-family: "Open Sans", sans-serif; background-color: rgb(241, 250, 244);">2 using <1 mol-% metal.